Penilaian Kinerja Pegawai melalui Komunikasi Interpersonal dan Kepemimpinan - Tunggayana, Bayu Samara; Kurhayadi, Kurhayadi; Susniwati, Susniwati (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2023)
Employee performance is an important factor to achieve the success and efficiency of an organization. Several factors were identified regarding the problems that occur in employee performance. This study aims to determine the effect of interpersonal communication and sub-district leadership on employee performance in the Rancasari sub-district, Bandung city. This study used a quantitative approach using surveys and questionnaires to collect data from a sample of 34 employees. The data analysis technique used to test the findings in this study is multiple regression analysis with the help of SPSS software. The results of this study indicate that interpersonal communication and sub-district leadership have a positive effect on employee performance in the Rancasari sub-district in Bandung city. The results of this study make a practical contribution to workers in the Rancasari sub-district to always build an organizational climate by creating better and more effective communication.